The role of purinergic P2Y(12) and P2Y(13) receptors in ADPβS-induced inhibition of the cardioaccelerator sympathetic drive in pithed rats - Villanueva-Castillo, Belinda (Purinergic Signal, 2020)
ATP is a cotransmitter released with other neurotransmitters from sympathetic nerves, where it stimulates purinergic receptors. Purinergic adenosine P(1) receptors (coupled to G(i/o) proteins) produce sympatho-inhibition in several autonomic effectors by prejunctional inhibition of neurotransmitter release. Similarly, signalling through P2Y(12) and P2Y(13) receptors coupled to G(i/o) proteins is initiated by the ATP breakdown product ADP. Hence, this study has pharmacologically investigated a possible role of ADP-induced inhibition of the cardioaccelerator sympathetic drive in pithed rats, using a stable ADP analogue (ADPβS) and selective antagonists for the purinergic P2Y(1), P2Y(12) and P2Y(13) receptors. Accordingly, male Wistar rats were pithed and: (i) pretreated i.v. with gallamine (25 mg/kg) and desipramine (50 μg/kg) for preganglionic spinal (C(7)-T(1)) stimulation of the cardioaccelerator sympathetic drive (n = 78); or (ii) prepared for receiving i.v. injections of exogenous noradrenaline (n = 12). The i.v. continuous infusions of ADPβS (10 and 30 μg/kg/min) dose-dependently inhibited the tachycardic responses to electrical sympathetic stimulation, but not those to exogenous noradrenaline. The cardiac sympatho-inhibition produced by 30 μg/kg/min ADPβS was (after i.v. administration of compounds) (i) unchanged by 1-ml/kg bidistilled water or 300-μg/kg MRS 2500 (P2Y(1) receptor antagonist), (ii) abolished by 300-μg/kg PSB 0739 (P2Y(12) receptor antagonist) and (iii) partially blocked by 3000-μg/kg MRS 2211 (P2Y(13) receptor antagonist). Our results suggest that ADPβS induces a cardiac sympatho-inhibition that mainly involves the P2Y(12) receptor subtype and, probably to a lesser extent, the P2Y(13) receptor subtype. These receptors may represent therapeutic targets for treating cardiovascular pathologies, including stroke and myocardial infarctions.